The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/insects10110380
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Larvae of the Solitary Bee Osmia bicornis to the Honey Bee Pathogen Nosema ceranae Affects Life History

Abstract: Wild bees are important pollinators of wild plants and agricultural crops and they are threatened by several environmental stressors including emerging pathogens. Honey bees have been suggested as a potential source of pathogen spillover. One prevalent pathogen that has recently emerged as a honey bee disease is the microsporidian Nosema ceranae. While the impacts of N. ceranae in honey bees are well documented, virtually nothing is known about its effects in solitary wild bees. The solitary mason bee Osmia bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 96 publications
0
13
1
Order By: Relevance
“…The effects of microsporidia infections in honeybees and bumblebees includes wing deformity, reduced foraging efficiency, reduced colony fitness and increased mortality, with N. bombi being found in multiple species of bumblebees and N. ceranae found in bumblebees and honeybees 65 71 In addition N. ceranae may be able to infect the mason bee, Osmia bicornis 72 . While this study did not find impacts on survival, a similar study that assessed impacts of N. ceranae on larval O. bicornis did find negative impacts on survival 73 . The trypanosomatids are mostly Crithidia species whose cells are transmitted via the fecal-oral route.…”
Section: Methodscontrasting
confidence: 75%
“…The effects of microsporidia infections in honeybees and bumblebees includes wing deformity, reduced foraging efficiency, reduced colony fitness and increased mortality, with N. bombi being found in multiple species of bumblebees and N. ceranae found in bumblebees and honeybees 65 71 In addition N. ceranae may be able to infect the mason bee, Osmia bicornis 72 . While this study did not find impacts on survival, a similar study that assessed impacts of N. ceranae on larval O. bicornis did find negative impacts on survival 73 . The trypanosomatids are mostly Crithidia species whose cells are transmitted via the fecal-oral route.…”
Section: Methodscontrasting
confidence: 75%
“…Considering solitary bees, knowledge about their natural and healthy microbiomes advanced in the recent years [ 19 , 20 , 21 , 22 , 23 , 24 ]. Studies investigating potential microbial pathogens, however, focused on infections that are common between honey bees or bumble bees and solitary bees [ 25 , 26 , 27 ]. While studies investigated non-lethal endosymbionts in solitary bees, e.g., Wolbachia [ 28 ], dedicated studies screening for potential bacterial pathogens and other harmful bacteria in solitary bees specifically are currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Most bee species within a community can be exposed to numerous pathogens when foraging at flowers, including C. bombi (Figueroa et al ., 2020; Graystock et al ., 2020). Our results support a growing body of literature indicating the need to assess the host range of bee pathogens, including assessments of replication and impacts on survival (Bramke et al ., 2019; Müller et al ., 2019). The presence of C. bombi in bee feces has been used to identify active infections in bumble bees (Imhoof and Schmid-Hempel, 1999), where it can be detected in as quickly as 5 days post-inoculation (Logan et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This includes pathogens known to infect honey bees and bumble bees (Apidae), including Apicystis bombi , Ascosphaera spp., C. bombi , C. mellificae , N. ceranae and numerous viruses (Singh et al ., 2010; Evison et al ., 2012; Ravoet et al ., 2014; Schoonvaere et al ., 2018; Figueroa et al ., 2020). However, except for single-stranded RNA viruses which allow for strand-specific PCR assays to detect viral replication, we currently cannot distinguish between transient passage through the bee gut and active infections, nor do we know if there are negative consequences for the host based solely on molecular screenings (Bramke et al ., 2019). Some existing studies that have experimentally evaluated the impacts on solitary bee health have shown increased mortality associated with infections [e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation